Treatment Failure in Urinary Tract Infections: A Warning Witness for Virulent Multi-Drug Resistant ESBL- Producing Escherichia coli - Naziri, Zahra; Derakhshandeh, Abdollah; Soltani Borchaloee, Arash; Poormaleknia, Meisam; Azimzadeh, Negar (Infection and drug resistance, 2020)
Global increase in the prevalence of virulent extended-spectrum beta-lactamase (ESBL)-producing uropathogenic (UPEC), which is also multi-drug resistant (MDR), leads to increase in severity of urinary tract infections (UTIs), decrease in the efficacy of the first-line antibiotics, and therefore increase in the morbidity and mortality rates. We investigated the distribution of ESBL-producing UPEC in 78 isolates from community-acquired UTI patients in southern Iran. The prevalence of three major ESBL genes, antimicrobial resistance patterns against 15 conventional antibiotic disks, and the presence of 11 important virulence genes that involve in the development and progression of UTIs were evaluated in these isolates. Of the UPECs, 34.6% were ESBL-positive and 96.3% of the ESBL-producers were MDR. Among the ESBL-producers, 100% harbored , 63% harbored , and 11.1% harbored genes. ESBL-producers showed a higher level of resistance to the tested cephalosporins, fluoroquinolones, trimethoprim-sulfamethoxazole, and tetracycline than non-ESBL producers. All isolates were resistant to the tested penicillins. Prevalence of resistance to about two-third of the tested antibiotics was higher than 50% and 93.6% of the isolates were MDR. High prevalence of virulence factors particularly the adhesins (82.1% , 73.1% genes) and siderophore (73.1% gene) was seen in the UPECs. But fortunately in MDR isolates, the virulence score and prevalence of hemagglutinin ( ), hemolysin toxin ( ) and invasin ( ) genes were lower than in non-MDR UPECs. Shockingly, among the 15 common antibiotics, only nitrofurantoin (<20% resistance) could be recommended as an appropriate drug for the treatment of UTIs due to our ESBL-producer UPECs. The alarming level of virulent MDR ESBL-producer strains in this study necessitates the performing of an antibiotic stewardship program, regional screening of ESBL-producers and their virulence properties to select appropriate antibiotic, or designing new therapeutic methods for UTIs by inactivation of the essential virulence factors of UPECs.